The boss from outer space and other aliens at work : a down-to-earth guide for getting along with just about anyone - Addesso, Patricia J. (American Management Association, 2007)
"If you work in an office, chances are you have to deal with at least some people who are so different they might as well be from another planet. Packed with realistic strategies, The Boss from Outer Space and Other Aliens at Work shows you how to gain a greater understanding of even your most difficult co-workers, categorizing different personality types in terms of the planets. (Is your co-worker a nonconformist? Then he's from Saturn, with its distinctive rings!) You'll learn how to relate to, appreciate, and get more from your relationship with every type of person under the sun in this fun and easy-to-read - yet enormously practical - book."--Jacket.